Perceptions on utilization, population, and factors that affecting local distribution of Mimusops zeyheri in the Vhembe Biosphere Reserve, South Africa - NONHLANHA PRUDENCE LUBISI; LUAMBO JEFFREY RAMARUMO; MUELETSHEDZI MANYAGA; WILFRED OTANG MBENG; SALMINA MOKGEHLE (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lubisi NP, Ramarumo LJ, Manyaga M, Mbeng WO, Mokgehle S. 2023. Perceptions on utilization, population, and factors that affecting local distribution of Mimusops zeyheri in the Vhembe Biosphere Reserve, South Africa. Biodiversitas 24: 6432-6439. Mimusops zeyheri Sond., was once an important plant species to local communities in Southern Africa but nowadays is considered as underutilized plant. Undoubtedly, the neglect of indigenous knowledge associated with M zeyheri could lead to its gradual disappearance. This study aimed to evaluate local people‘s perceptions about the contribution of M. zeyheri to their livelihoods, population status and factors affecting its local distributions in the Vhembe Biosphere Reserve, Limpopo Province, South Africa. Semi-structured research questionnaires were administered to 52 randomly selected respondents. The majority of respondents (67.31%) perceived the decline in the population of M. zeyheri within the studied sites. More than three-quarters of laypeople (78.6%), two-thirds of farmers (66.7%), and 57.1% of environmentalists stated that M. zeyheri possessed more economic benefits than other livelihood benefits. A total percentage of 44.20% of participants perceived fire as the main factor that negatively affects the distribution of M. zeyheri in the studied regions. Documenting information about people's perceptions regarding the contributions of M. zeyheri to local livelihoods and assessing factors that affect its local distribution is a fundamental step toward understanding its associated sociocultural values, socio-economic, and threats. Future studies should incorporate both ethnobotanical and ecological data-gathering methods and validations.